Cognitive Behavior Counseling to Improve Responsibility Attitudes: A Development of Guidebooks - Ni Made Desi Ernayanti; Nyoman Dantes; Kadek Suranata (Bisma The Journal of Counseling, 2020)
This research was conducted to find out the procedures for implementing cognitive behavioral counseling models to improve the attitude of responsibility of high school students and to determine the validity of the contents of the cognitive behavioral counseling guide. Research conducted is research and development or research and development (R&D), the research model used is Four-D (4D). The 4D model consists of four stages of research namely define, design, develop, and disseminate. Data analysis to test the validity of the manual book product content using the Lawshe CVR and CVI formulas. Testing for products is carried out by 5 experts or experts who are competent in the field of Counseling Guidance. The results of the study based on content validity are CVR values per item +1 to 0 (CVR> 0). Thus, the results of the Lawshe CVI analysis obtained 0.79 greater than 0 (0.79> 0). Based on the analysis of these data the validity value of the contents of this guide product is high.